FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. SMART TALENTA MULTITAMA - Yerni Retno Rahayu; Ary Sutrischastini (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to 1) analyze the effect of supervision on employee performance at PT. Smart Talent Multitama; 2) analyze the effect of motivation on employee performance at PT. Smart Talent Multitama; 3) analyze the influence of supervision and motivation on employee performance at PT. Smart Talent Multitama. This research method uses a quantitative approach, with data collection techniques in the form of a questionnaire. The population is all employees of PT. Smart Talenta Multitama totaling 45 employees and all of these employees were used as respondents. Technical analysis of data using multiple linear regression processed with SPSS version 20. The results obtained are 1) Supervision has a positive and significant effect on employee performance when viewed from a significant less than 0.05; 2) Motivation has a positive and significant effect on employee performance when viewed from a significant less than 0.05 and 3) Taken together, supervision and motivation have a positive and significant effect on the performance of PT. Smart Talent Multitama.